(untitled) (Research, Society and Development, 2021)
Ovariohysterectomy is an important procedure for health and walfare animal, even as for society. However, during the procedure there is a predisposition of the animal to hypothermia, due to the anesthesia and surgery. In order to study the effect of hydraulic radiant floor on the body temperature of female dogs submitted to ovaryiohysterectomy, 130 animals, coming from the Araquari Animal Castration and Identification Center (CCIAA), were evaluated. Physiological parameters were collected, such as color of the oral mucosa, rectal temperature, respiratory and heart rate in animals housed in pen with hydraulic radiant floor (CP) and blanket (SP). The evaluations took place between the period of entry of the animal (T0) in the CCIAA until its return to home (T4). To analyze the relationship between the physiological parameters and the physical development of the animal, subgroups were created: one based on size (small, medium and large) and other on age (young and adults). The relationship between physiological parameters and room temperature was studied by dividing the experimental period into cold, moderate and warm days. The results were subjected to chi-square and variance analysis for non-normal data. The analyzes were made at the level of 5% probability of error. The hydraulic radiant floor proved to be efficient in anesthetic recovery of animals, regardless of the size and age. In addition, there was a greater need for the heating system on days with low temperatures. We conclude that the hydraulic radiant floor is an effective and safe way for heating and to prevent hypothermia in the postoperative period.